The Influence of Product Quality, Price, and Promotion on the Purchase Decision of Honda Motorcycles - Fandholi, Achmad Fany; Febryantahanuji, Febryantahanuji (Dinasti Publisher, 2025)
This study aims to analyze the influence of product quality, price, and promotion on the purchasing decisions of Honda motorcycles, and to identify the most dominant influencing variable. This research is quantitative with a case study on Honda Matic motorcycle users in the city of Blora. The sampling was conducted using a purposive sampling technique with a total of 110 respondents. Data were collected through questionnaires and analyzed using multiple linear regression analysis with the SPSS software. The results of the study show that: (1) Product quality has a positive and significant effect on purchasing decisions. (2) Price has no significant effect on purchasing decisions. (3) Promotion has a positive and significant effect on purchasing decisions. (4) Product quality, price, and promotion simultaneously have a significant effect on purchasing decisions. The analysis also found that promotion is the most dominant variable influencing the purchasing decisions of Honda Matic motorcycles in the city of Blora. The coefficient of determination (R²) indicates that 41.7% of the purchasing decision variable can be explained by the variables of product quality, price, and promotion, while the remainder is influenced by other factors outside this study.